Pengaruh Jenis Salak (Salacca edulis R.) dan Konsentrasi Gula Terhadap Karakteristik Wine - Sonya Purnama Sari, Ni Putu; Wisaniyasa, Ni Wayan; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
Wine was a fermented drink made of grapes extract. However, wine could be made from other fruits that contain glucose, such as snake fruit. Making wine from snack fruit was an alternative to overcome the abundance of snake fruit at its harvest time. The making of snake fruit wine was done by giving treatment about different types of snake fruit and sugar concentration that was used to produce wine with the best characteristics. The purpose of this research was to determine the effect of different types of snake fruit and sugar concentration on the characteristics of snake fruit wine, as well as to determine the different types of snake fruit and sugar concentration that can produce snake fruit wine with the best characteristics. This research used Factorial Completely Randomized Design with two factors. The first factor was the type of snake fruit, namely: Salak Gula Pasir, Salak Nangka, and Salak Pondoh. The second factor was sugar concentration, namely: 20%, 25%, and 30%. The result of this snake fruit wine tested for its alcohol level (ethanol), reducing sugar, total acid, acidity (pH), total soluble solid, sensory assessment including color, taste, smell, and overall acceptance. The result showed that interaction of the types of snake fruit and sugar concentration had a significant effect (P<0,05) on alcohol level (ethanol), reducing sugar, total acid, total soluble solid, also taste and overall acceptance (hedonic). The best characteristics of the wine was obtained from the treatment of Salak Pondoh type and the concentration of sugar 30% with 10,86% ethanol level, 0,94% reducing sugar, 0,33% total acid, pH 3,47, total soluble solid 13,65 °Brix, sensory assessment of color was preferred, the aroma was ordinary with characteristic slightly distinctive aroma of snake fruit, the taste was preferred, and the overall acceptance was preferred.